Method for optimizing laser damage resistance of a variable refractive index film

CN122926696APending Publication Date: 2026-10-16YANGZHOU KELAI PHOTOELECTRIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511264344.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-05
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而现有GRIN薄膜技术仍存在三方面核心瓶颈:其一,折射率梯度设计多采用线性或指数型单一模式,难以适应不同波长激光(如紫外到红外)或超短脉冲(飞秒级)与连续波激光的差异化需求;其二,制备工艺中膜层界面处易因材料相容性差异产生缺陷,导致损伤阈值出现批次性波动;其三,非均匀折射率分布引发的热应力分布不均问题未得到根本解决,长期服役条件下仍存在脱层或裂纹扩展风险

Benefits of technology

[0022] I. Optimized Refractive Index Distribution Model: In the constructed refractive index distribution model, the surface layer of the thin film is set as a linearly decreasing refractive index layer, the main body of the thin film is set as a parabolic refractive index layer, and the bottom layer of the thin film is set as a low refractive index buffer layer. This non-uniform refractive index distribution can more effectively control the optical field, reduce the peak laser energy density, and reduce the electric field concentration effect, thereby increasing the damage threshold of the thin film. For example, traditional uniform refractive index thin films are prone to electric field concentration at the film interface or defects under laser irradiation, while the variable refractive index distribution of this invention can avoid this situation, enabling the thin film to withstand higher energy lasers without damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122926696A_ABST
    Figure CN122926696A_ABST
Patent Text Reader

Abstract

The application discloses a kind of variable refractive index film laser damage resistance performance optimization method, it is related to thin film technical field, its technical points are: first step is to build refractive index distribution model, thin film surface layer accounts for 0~20% of total thickness, is linearly decreasing refractive index layer;Thin film main body accounts for 20%~80%, is parabolic refractive index layer;Thin film bottom layer accounts for 0%~80%, is low refractive index buffer layer.Second step is to use multi-target material co-deposition technology, simultaneously control high, low refractive index material deposition rate gradient regulation refractive index.Third step is to use dynamic temperature field control when depositing, and infrared heating and low temperature cooling cycle are used to inhibit film layer defect.Fourth step is to dope nano-particle in parabolic refractive index layer, and set gradient thermal expansion coefficient, so that the thermal expansion coefficient of thin film main body is gradually matched with the change of surface layer to bottom layer.The application can significantly improve the damage threshold and stability of thin film in strong laser environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thin film technology, and in particular to a method for optimizing the laser damage resistance of variable refractive index thin films. Background Technology

[0002] Traditional optical thin-film devices (such as single-layer or homogeneous multilayer dielectric films) face fundamental challenges in resisting laser damage when applied in high-energy laser systems. Due to the limited optical field manipulation capability resulting from a uniform refractive index distribution, laser irradiation easily induces electric field concentration effects at film interfaces or defects, accompanied by the accumulation of thermal stress in localized areas. Inherent material defects (such as pinholes and impurities) further lower the damage threshold, making the films susceptible to peeling, melting, or ablation under strong laser irradiation, severely limiting their reliability in cutting-edge fields such as high-power laser weapons and inertial confinement fusion.

[0003] Variable refractive index thin films (GRIN) achieve active control of the optical field distribution through continuous refractive index gradient design, effectively reducing the peak laser energy density and optimizing thermal stress distribution, thus being regarded as an important direction to overcome the limitations of traditional thin films. However, existing GRIN thin film technology still has three core bottlenecks: First, the refractive index gradient design mostly adopts a linear or exponential single mode, which is difficult to adapt to the differentiated requirements of different wavelength lasers (such as ultraviolet to infrared) or ultrashort pulses (femtosecond) and continuous wave lasers; Second, defects are easily generated at the film interface due to differences in material compatibility during the fabrication process, resulting in batch-to-batch fluctuations in the damage threshold; Third, the problem of uneven thermal stress distribution caused by non-uniform refractive index distribution has not been fundamentally solved, and there is still a risk of delamination or crack propagation under long-term service conditions.

[0004] The aforementioned technical bottlenecks indicate that existing optical thin film technologies cannot simultaneously meet the comprehensive requirements of high-energy laser systems for damage threshold, wavelength adaptability, and long-term stability. Summary of the Invention

[0005] In order to at least solve one of the above-mentioned technical problems, the present invention aims to provide a method for optimizing the laser damage resistance of variable refractive index thin films, which significantly improves the damage threshold and stability of thin films in strong laser environments.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] A method for optimizing the laser damage resistance of variable refractive index thin films includes the following steps:

[0008] The first step is to construct a model of the refractive index distribution, which includes:

[0009] The thin film surface layer accounts for 0-20% of the total thickness and is designed as a linearly decreasing refractive index layer, that is, its refractive index decreases linearly.

[0010] The thin film body accounts for 20% to 80% of the total thickness and is designed as a parabolic refractive index layer, that is, its refractive index decreases parabolically.

[0011] The first step involves a low-refractive-index buffer layer, comprising 0% to 80% of the total thickness. The second step employs multi-target co-deposition technology, simultaneously controlling the deposition rates of high-refractive-index and low-refractive-index materials to regulate the refractive index gradient. The third step utilizes dynamic temperature field control during deposition, employing infrared heating and low-temperature cooling cycles to suppress film defect formation. The fourth step involves doping the parabolic refractive index layer with nanoparticles and setting a gradient thermal expansion coefficient, ensuring that the thermal expansion coefficient of the main film layer gradually matches the change in thermal expansion coefficient from the film surface to the bottom layer.

[0012] Preferably, the size of the nanoparticles doped in the fourth step is ≤20nm, the nanoparticles are Al2O3 or ZrO2, and the doping concentration of the nanoparticles is 0.5~5vol.

[0013] Preferably, the nanoparticle doping process employs in-situ chemical vapor deposition (CVD) or sol-gel method, and ultrasonic-assisted dispersion is applied during the deposition process to control the uniformity deviation of nanoparticles within the film matrix to ≤5%.

[0014] Preferably, the multi-target co-deposition technology employs an ion beam-assisted deposition process, which controls the continuous change of the refractive index gradient by simultaneously adjusting the deposition rates of high-refractive-index materials and low-refractive-index materials, combined with ion beam energy control.

[0015] Preferably, the high refractive index material is TiO2, and the low refractive index material is SiO2.

[0016] Preferably, the difference Δn between the initial refractive index of the thin film surface layer and the refractive index of the thin film bottom layer satisfies 1.0≤Δn≤1.5, wherein the initial refractive index of the thin film surface layer is determined by a high refractive index material, and the refractive index of the thin film bottom layer is determined by a low refractive index buffer layer material.

[0017] Preferably, the specific measures for controlling the dynamic temperature field are as follows: during the deposition process, infrared heating and liquid nitrogen cooling are alternately activated, with the infrared heating temperature range being 80~200℃ and the liquid nitrogen cooling temperature range being −50~0℃.

[0018] Preferably, the alternation cycle of infrared heating and low-temperature cooling in the dynamic temperature field control is 5 to 30 minutes, and the heating rate of infrared heating and the cooling rate of liquid nitrogen cooling are both controlled at 5 to 20°C / min.

[0019] Preferably, the gradient thermal expansion coefficient is achieved by adjusting the doping concentration of multilayer nanoparticles within the thin film body, wherein the thermal expansion coefficient of the surface layer of the thin film is set as α1, and the thermal expansion coefficient of the bottom layer of the thin film is set as α2, where α1>α2.

[0020] Preferably, the underlying material of the thin film is fused silica, glass, or a crystalline material.

[0021] The present invention has the following beneficial effects:

[0022] I. Optimized Refractive Index Distribution Model: In the constructed refractive index distribution model, the surface layer of the thin film is set as a linearly decreasing refractive index layer, the main body of the thin film is set as a parabolic refractive index layer, and the bottom layer of the thin film is set as a low refractive index buffer layer. This non-uniform refractive index distribution can more effectively control the optical field, reduce the peak laser energy density, and reduce the electric field concentration effect, thereby increasing the damage threshold of the thin film. For example, traditional uniform refractive index thin films are prone to electric field concentration at the film interface or defects under laser irradiation, while the variable refractive index distribution of this invention can avoid this situation, enabling the thin film to withstand higher energy lasers without damage.

[0023] II. Multi-target co-deposition technology: This technology employs multi-target co-deposition to achieve precise control of the refractive index gradient by simultaneously controlling the deposition rates of high-refractive-index and low-refractive-index materials. Unlike existing technologies with a single refractive index gradient design mode, this precise control can better adapt to the differentiated requirements of different wavelength lasers and ultrashort pulse and continuous wave lasers, further improving the film's laser tolerance and increasing the damage threshold.

[0024] III. Dynamic Temperature Field Control: Dynamic temperature field control is employed during the deposition process, using infrared heating and low-temperature cooling cycles to suppress the formation of film defects. Inherent material defects (such as pinholes and impurities) lower the damage threshold of the film. This method reduces defect generation through dynamic temperature field control, thereby indirectly improving the film's resistance to laser damage and increasing the damage threshold.

[0025] IV. Doping with Nanoparticles and Setting a Gradient Thermal Expansion Coefficient: Nanoparticles are doped into the parabolic refractive index layer, and a gradient thermal expansion coefficient is set so that the thermal expansion coefficient of the bulk film changes stepwise to match the change in thermal expansion coefficient from the surface layer to the bottom layer of the film. The uneven thermal stress distribution caused by non-uniform refractive index distribution can lower the damage threshold of the film. This method optimizes the thermal stress distribution through this design, reducing damage caused by thermal stress concentration and improving the damage threshold.

[0026] Fifth, the constructed refractive index distribution model and the multi-target co-deposition technology adopted can better adapt to the needs of different wavelength lasers (such as ultraviolet to infrared). Traditional GRIN thin film technology has a single refractive index gradient design, which is difficult to meet the requirements of different wavelength lasers. However, this invention, through precise refractive index distribution design and gradient control, enables the thin film to effectively control the light field under different wavelength laser irradiation, reduce the peak energy density, and thus enhance the adaptability of the thin film to different wavelength lasers.

[0027] VI. Suppressing Film Defect Formation: Dynamic temperature field control using infrared heating and low-temperature cooling cycles suppresses film defect formation during deposition. Defects at the film interface are prone to occur due to material compatibility differences during the fabrication process, leading to batch-to-batch fluctuations in the damage threshold and affecting the long-term stability of the film. This method reduces defect formation, lowers the risk of batch-to-batch fluctuations, and improves the stability of film quality, thereby enhancing its long-term service reliability.

[0028] VII. Optimization of Thermal Stress Distribution: By doping nanoparticles into the parabolic refractive index layer and setting a gradient thermal expansion coefficient, the thermal expansion coefficient of the bulk film gradually changes to match the change in thermal expansion coefficient from the film surface to the bottom layer, thus solving the problem of uneven thermal stress distribution caused by non-uniform refractive index distribution. Under long-term service conditions, uneven thermal stress distribution can easily lead to delamination or crack propagation. This method optimizes the thermal stress distribution, reduces the risk of delamination and crack propagation, and improves the long-term stability of the film.

[0029] 8. Synergy between Multi-Target Co-deposition and Dynamic Temperature Field Control: Multi-target co-deposition technology enables precise control of the refractive index gradient, while dynamic temperature field control suppresses the formation of film defects. The synergistic effect of these two technologies ensures the refractive index distribution required for the film to have excellent resistance to laser damage, while reducing performance degradation caused by defects, enabling the film to perform more stably under strong laser environments.

[0030] IX. Combination of Doped Nanoparticles and Gradient Thermal Expansion Coefficient: Doping nanoparticles with a gradient thermal expansion coefficient in a parabolic refractive index layer can influence the optical and thermal properties of the thin film. The gradient thermal expansion coefficient further optimizes the thermal stress distribution. This combination not only improves the laser damage threshold of the thin film but also enhances its long-term stability, enabling the film to maintain good performance under complex working environments. Attached Figure Description

[0031] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0032] Figure 1 This is an electron microscope image (15000x) of a thin film cross-section according to the first embodiment of the present invention. Detailed Implementation

[0033] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] Example 1

[0035] Constructing a refractive index distribution model:

[0036] The total thickness of the thin film is set to 500 nm. The surface layer of the thin film is 100 nm thick (accounting for 20% of the total thickness) and is set as a linearly decreasing refractive index layer, which linearly decreases from a high refractive index (TiO2, initial refractive index of about 2.3) to an intermediate refractive index.

[0037] The main body of the thin film has a thickness of 300 nm (accounting for 60% of the total thickness) and is designed as a parabolic refractive index layer, with the refractive index decreasing from the middle refractive index parabola to the low refractive index.

[0038] The bottom layer of the thin film has a thickness of 100 nm (accounting for 20% of the total thickness) and is set as a low refractive index buffer layer (SiO2, refractive index of about 1.46).

[0039] Multi-target co-deposition technology: This technology employs an ion beam-assisted deposition process, using TiO2 as the high-refractive-index material and SiO2 as the low-refractive-index material. The deposition rates of both materials are simultaneously adjusted, and combined with ion beam energy control (set to 100 eV), continuous variation of the refractive index gradient is achieved.

[0040] Dynamic temperature field control: Infrared heating and liquid nitrogen cooling are alternately activated during the deposition process. The infrared heating temperature is set to 80℃, and the liquid nitrogen cooling temperature is set to -30℃.

[0041] Nanoparticle doping and gradient thermal expansion coefficient setting: 10 nm Al₂O₃ nanoparticles were doped into a parabolic refractive index layer at a doping concentration of 0.5 vol%. By adjusting the doping concentration of multiple nanoparticles within the bulk film, the thermal expansion coefficient α₁ of the film surface was achieved to be 8 × 10⁻⁻⁶. 6 / ℃, the coefficient of thermal expansion of the thin film substrate α2 = 3×10⁻ 6 / ℃, the coefficient of thermal expansion of the film body changes step by step to match the change from the surface layer to the bottom layer. The bottom layer material of the film is fused silica.

[0042] Example 2

[0043] Constructing a refractive index distribution model:

[0044] The total thickness of the thin film is set to 600 nm. The surface layer of the thin film is 60 nm thick (accounting for 10% of the total thickness) and is set as a linearly decreasing refractive index layer, which linearly decreases from high refractive index (TiO2) to intermediate refractive index.

[0045] The main body of the thin film has a thickness of 420 nm (accounting for 70% of the total thickness) and is designed as a parabolic refractive index layer, with the refractive index decreasing from the middle refractive index parabola to the low refractive index.

[0046] The bottom layer of the thin film has a thickness of 120 nm (accounting for 20% of the total thickness) and is set as a low refractive index buffer layer (SiO2).

[0047] Multi-target co-deposition technology: This technique employs an ion beam-assisted deposition process, using TiO2 as the high-refractive-index material and SiO2 as the low-refractive-index material. The deposition rates of both materials are simultaneously adjusted, and combined with ion beam energy control (set to 150 eV), a continuous variation of the refractive index gradient is achieved.

[0048] Dynamic temperature field control: Infrared heating and liquid nitrogen cooling are alternately activated during the deposition process. The infrared heating temperature is set to 140℃, and the liquid nitrogen cooling temperature is set to -50℃.

[0049] Nanoparticle doping and gradient thermal expansion coefficient setting: ZrO2 nanoparticles with a size of 15 nm were doped into a parabolic refractive index layer at a doping concentration of 2.5 vol%. By adjusting the doping concentration of multiple nanoparticles within the bulk film, the thermal expansion coefficient α1 of the film surface was achieved to be 9 × 10⁻⁻⁶. 6 / ℃, the coefficient of thermal expansion of the thin film substrate α2 = 4×10⁻ 6 / ℃, the coefficient of thermal expansion of the film body changes step by step to match the change from the surface layer to the bottom layer. The bottom layer material of the film is glass.

[0050] Example 3

[0051] Constructing a refractive index distribution model:

[0052] The total thickness of the thin film is set to 700 nm. The surface layer of the thin film has a thickness of 140 nm (accounting for 20% of the total thickness) and is set as a linearly decreasing refractive index layer, which linearly decreases from high refractive index (TiO2) to intermediate refractive index.

[0053] The main body of the thin film has a thickness of 420 nm (accounting for 60% of the total thickness) and is designed as a parabolic refractive index layer, with the refractive index decreasing from the middle refractive index parabola to the low refractive index.

[0054] The thickness of the bottom layer of the thin film is 140 nm (accounting for 20% of the total thickness), and it is set as a low refractive index buffer layer (SiO2).

[0055] Multi-target co-deposition technology: This technique employs an ion beam-assisted deposition process, using TiO2 as the high-refractive-index material and SiO2 as the low-refractive-index material. The deposition rates of both materials are simultaneously adjusted, and combined with ion beam energy control (set to 200 eV), a continuous variation of the refractive index gradient is achieved.

[0056] Dynamic temperature field control: Infrared heating and liquid nitrogen cooling are alternately activated during the deposition process. The infrared heating temperature is set to 200℃, and the liquid nitrogen cooling temperature is set to 0℃.

[0057] Nanoparticle doping and gradient thermal expansion coefficient setting: Al₂O₃ nanoparticles with a size of 20 nm were doped into a parabolic refractive index layer at a doping concentration of 5 vol%. By adjusting the doping concentration of multiple nanoparticles within the bulk film, the thermal expansion coefficient α₁ of the film surface was achieved to be 10 × 10⁻⁻⁶. 6 / ℃, the coefficient of thermal expansion of the thin film substrate α2 = 5×10⁻ 6 / ℃, the coefficient of thermal expansion of the film substrate changes stepwise to match the change from the surface layer to the bottom layer. The bottom layer material of the film is a crystalline material.

[0058] Experimental Project

[0059] 1. Thin film preparation experiment

[0060] Objective: To control the film thickness, the proportion of surface layer thickness, and the concentration of nanoparticle doping.

[0061] method:

[0062] Physical vapor deposition (PVD): The total thickness of the film (e.g., 500-700 nm) is controlled by adjusting the deposition time, power and gas pressure.

[0063] Ion beam assisted deposition (IBAD): Adjusting the ion beam energy (100-200 eV) and beam current density to optimize the surface structure.

[0064] Co-sputtering or doping process: Nanoparticles (Al2O3 or ZrO2) are introduced during the deposition process, and the doping concentration (0.5-5 vol%) is adjusted by controlling the sputtering target ratio or gas flow rate.

[0065] 2. Nanoparticle control experiments

[0066] Objective: To achieve precise control over the size (10-20 nm) and type of nanoparticles.

[0067] method:

[0068] Sol-gel method: Particle size is controlled by adjusting the precursor concentration, annealing temperature (e.g., liquid nitrogen cooling to -50°C to 0°C), and holding time.

[0069] Chemical vapor deposition (CVD): Synthesizing specific types of nanoparticles by selecting different metal-organic sources (such as aluminum or zirconium sources).

[0070] In-situ TEM observation: Real-time monitoring of nanoparticle nucleation and growth processes to verify size distribution uniformity.

[0071] 3. Thermal expansion coefficient (α1, α2) test

[0072] Objective: To measure the thermal expansion behavior of materials within different temperature ranges.

[0073] method:

[0074] Thermomechanical analyzer (TMA): Applyes a constant load during heating / cooling, records dimensional changes, and calculates the linear coefficient of thermal expansion (×10⁻⁻⁴). 6 / ℃).

[0075] Laser interferometry: This method uses a high-precision laser displacement sensor to measure the deformation of a thin film during temperature cycling, distinguishing between α1 (low temperature range) and α2 (high temperature range).

[0076] 4. Damage threshold test

[0077] Objective: To evaluate the material's resistance to laser damage.

[0078] method:

[0079] 1-on-1 pulsed laser test: Using a nanosecond or picosecond laser, gradually increase the energy density (J / cm²) until surface damage (such as cracks or peeling) is observed.

[0080] R-on-1 fatigue test: Low-energy pulses are applied to the same location multiple times, and the relationship between damage probability and energy density is statistically analyzed.

[0081] 5. Long-term stability test

[0082] Objective: To verify the durability of materials under extreme environments.

[0083] method:

[0084] High temperature and high humidity aging: Place the sample in an 85℃ / 85%RH environment and check for delamination or cracks regularly (e.g., observe with an optical microscope every 100 hours).

[0085] Thermal cycling test: Rapid temperature change (e.g., 10℃ / min) between -50℃ and 200℃ to simulate actual service conditions, and record the failure-free time (h).

[0086] As shown in Table 1, the following is a summary of the experimental results data.

[0087] Table 1 Experimental Data

[0088]

[0089] Experimental data analysis

[0090] Damage threshold:

[0091] Experimental data show that the damage threshold of the thin film gradually increases with the combined effects of increasing nanoparticle doping concentration (from 0.5 vol% in Example 1 to 5 vol% in Example 3), increased ion beam energy (from 100 eV to 200 eV), and increased infrared heating temperature (from 80 °C to 200 °C). This is because the non-uniform refractive index distribution in the constructed refractive index distribution model can more effectively control the optical field, reduce the peak laser energy density, and reduce the electric field concentration effect. Multi-target co-deposition technology precisely controls the refractive index gradient, better adapting to different laser requirements and improving tolerance. Dynamic temperature field control reduces defect generation, indirectly improving laser damage resistance. Doping with nanoparticles and setting a gradient thermal expansion coefficient optimizes the thermal stress distribution, reducing damage caused by thermal stress concentration. All these factors combined significantly improve the damage threshold.

[0092] Long-term stability:

[0093] Long-term stability time is extended with parameter optimization. Dynamic temperature field control suppresses film defect formation and reduces the risk of batch-to-batch fluctuations in damage threshold caused by defects due to material compatibility differences. Doping with nanoparticles and setting a gradient thermal expansion coefficient solves the problem of uneven thermal stress distribution caused by non-uniform refractive index distribution, reduces the risk of delamination and crack propagation, comprehensively improves the stability of film quality, and enhances its long-term service reliability.

[0094] Summary of technical principles and effects

[0095] Optimize the refractive index distribution model: By constructing a specific refractive index distribution model, the optical field can be effectively controlled by the non-uniform refractive index distribution, reducing the peak laser energy density, reducing the electric field concentration effect, increasing the damage threshold, and enhancing the adaptability to lasers of different wavelengths.

[0096] Multi-target co-deposition technology: Precisely controls the refractive index gradient to adapt to the differentiated needs of lasers of different wavelengths and ultrashort pulse and continuous wave lasers, further improving the film's tolerance to lasers and increasing the damage threshold.

[0097] Dynamic temperature field control: suppresses the formation of film defects, reduces batch-to-batch fluctuations in damage threshold caused by defects, improves film quality stability, and enhances long-term service reliability.

[0098] Doping with nanoparticles and setting a gradient thermal expansion coefficient: optimizes thermal stress distribution, reduces the risk of damage, delamination, and crack propagation caused by thermal stress concentration, and improves the damage threshold and long-term stability.

[0099] The above are merely specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent substitutions, or modifications made based on the present invention to solve essentially the same technical problems and achieve essentially the same technical effects are all covered within the protection scope of the present invention.

Claims

1. A method for optimizing the laser damage resistance of variable refractive index thin films, characterized in that, Includes the following steps: The first step is to construct a model of the refractive index distribution, which includes: The thin film surface layer accounts for 0-20% of the total thickness and is designed as a linearly decreasing refractive index layer, that is, its refractive index decreases linearly. The thin film body accounts for 20% to 80% of the total thickness and is designed as a parabolic refractive index layer, that is, its refractive index decreases parabolically. The first step involves a low-refractive-index buffer layer, comprising 0% to 80% of the total thickness. The second step employs a multi-target co-deposition technique, simultaneously controlling the deposition rates of high-refractive-index and low-refractive-index materials to regulate the refractive index gradient. The third step utilizes dynamic temperature field control during deposition, employing infrared heating and low-temperature cooling cycles to suppress film defect formation. The fourth step involves doping the parabolic refractive index layer with nanoparticles and setting a gradient thermal expansion coefficient, ensuring that the thermal expansion coefficient of the main film layer gradually matches the change in thermal expansion coefficient from the film surface to the bottom layer.

2. The method for optimizing the laser damage resistance of a variable refractive index thin film according to claim 1, characterized in that, In the fourth step, the size of the doped nanoparticles is ≤20nm, the nanoparticles are Al2O3 or ZrO2, and the doping concentration of the nanoparticles is 0.5~5vol.

3. The method for optimizing the laser damage resistance of a variable refractive index thin film according to claim 2, characterized in that, The nanoparticle doping process employs in-situ chemical vapor deposition (CVD) or sol-gel method, and ultrasonic-assisted dispersion is applied during the deposition process to control the uniformity deviation of nanoparticles within the film matrix to ≤5%.

4. The method for optimizing the laser damage resistance of a variable refractive index thin film according to claim 1, characterized in that, The multi-target co-deposition technology employs an ion beam-assisted deposition process, which controls the continuous change of the refractive index gradient by simultaneously adjusting the deposition rates of high-refractive-index and low-refractive-index materials and combining ion beam energy control.

5. The method for optimizing the laser damage resistance of a variable refractive index thin film according to claim 3, characterized in that, The high refractive index material is TiO2, and the low refractive index material is SiO2.

6. The method for optimizing the laser damage resistance of a variable refractive index thin film according to claim 1, characterized in that, The difference Δn between the initial refractive index of the film surface layer and the refractive index of the film bottom layer satisfies 1.0≤Δn≤1.5, wherein the initial refractive index of the film surface layer is determined by the high refractive index material, and the refractive index of the film bottom layer is determined by the low refractive index buffer layer material.

7. The method for optimizing the laser damage resistance of a variable refractive index thin film according to claim 1, characterized in that, The specific measures for dynamic temperature field control are as follows: during the deposition process, infrared heating and liquid nitrogen cooling are alternately activated, with the infrared heating temperature range being 80~200℃ and the liquid nitrogen cooling temperature range being −50~0℃.

8. The method for optimizing the laser damage resistance of a variable refractive index thin film according to claim 7, characterized in that, In the dynamic temperature field control, the alternation cycle of infrared heating and low-temperature cooling is 5 to 30 minutes, and the heating rate of infrared heating and the cooling rate of liquid nitrogen cooling are both controlled at 5 to 20℃ / min.

9. The method for optimizing the laser damage resistance of a variable refractive index thin film according to claim 1, characterized in that, The gradient thermal expansion coefficient is achieved by adjusting the doping concentration of multilayer nanoparticles within the film body. The thermal expansion coefficient of the film surface layer is set as α1, and the thermal expansion coefficient of the film bottom layer is set as α2, where α1>α2.

10. The method for optimizing the laser damage resistance of a variable refractive index thin film according to claim 1, characterized in that, The underlying material of the thin film is fused silica, glass, or a crystalline material.